Implementing and Analyzing Web Performance Testing for Universitas Terbuka’s Website with GTMetrix and Pingdom - Putri, Mayang Anglingsari (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
A higher education institution’s website allows lecturers and students to search for necessary information online. Good web performance is essential to provide better service to users. This research focuses on analyzing and testing the performance of a university website to maximize its efficiency. Performance testing measures a website’s effectiveness. In this study, we analyze the website of Universitas Terbuka (UT), known for its distance learning system. The goal is to assess the website’s performance using testing tools like GTMetrix and Pingdom, which automatically analyze web performance. These tools provide data on the website’s performance, which is then processed into information about strengths, weaknesses, and potential solutions. The outcome includes a comparison of performance metrics from GTMetrix and Pingdom. This research contributes to evaluating UT’s website performance and offers insights to help developers enhance and optimize the application to the desired level.